African women legends and the spirituality of resistance - Dube, Musa Wenkosi; Musili, Telesia K.; Owusu-Ansah, Sylvia (Routledge, 2024)
"This volume focuses on African indigenous women legends and their potential to serve as midwives for gender empowerment and for contributing towards African feminist theories. It considers the intersection of gender and spirituality in subverting patriarchy, colonialism, anthropocentricism, capitalism as well elevating African women to the social space of speaking as empowered subjects with public influence. The chapters examine historical, cultural, and religious African women legends who became champions of liberation and their approach to social justice. The authors suggest that the stories of resistance featured hold great potential for building justice-loving Earth Communities. The book will be of interest to scholars of religion, gender studies, Indigenous studies, African studies, African-Indigenous Knowledges and postcolonial studies"--